1996
DOI: 10.1016/0042-6989(96)00017-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide: A Review of Its Role in Retinal Function and Disease

Abstract: Nitric oxide synthase (NOS), the enzyme that catalyzes the formation of nitric oxide from L-arginine, exists in three major isoforms, neuronal, endothelial, and immunologic. Neuronal and endothelial isoforms are constitutively expressed, and require calcium for activation. Both of these isoforms can be induced (i.e., new protein synthesis occurs) under appropriate conditions. The immunologic isoform is not constitutively expressed, and requires induction usually by immunologic activation; calcium is not necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
206
0
9

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(219 citation statements)
references
References 138 publications
4
206
0
9
Order By: Relevance
“…The increase can be attributed to the dilation of retinal arterial vessels, by increased release of nitric oxide, through PDE5 inhibition (WRIGHT, 2006). Blood vessels are innervated by nitric oxide-producing neurons, which play an important role in local regulation of ocular blood fl ow, through the autonomic nervous system (GOLDSTEIN et al, 1996;TODA & NAKANISHI-TODA, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The increase can be attributed to the dilation of retinal arterial vessels, by increased release of nitric oxide, through PDE5 inhibition (WRIGHT, 2006). Blood vessels are innervated by nitric oxide-producing neurons, which play an important role in local regulation of ocular blood fl ow, through the autonomic nervous system (GOLDSTEIN et al, 1996;TODA & NAKANISHI-TODA, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ -dependent, neuronal NOS is moreover present in several parts of the retina, including photoreceptors (33,34), and in Purkinje cells (35). Given the high affinity of globins (36), including Ngb (37) for NO, one would expect Ngb to be in the Fe 2+ 7NO form inside NO-producing neurons.…”
Section: Neuroglobin As Scavenger Of Reactive Oxygen and Nitrogen Spementioning
confidence: 99%
“…Recently, we and others have reported that they die in diabetic retinopathy [20][21][22]. Nitric oxide (NO) is a molecule implicated in the pathogenic complications of diabetic retinopathy [23][24][25]. Yilmaz and coworkers [26] reported a fivefold elevation of NO in the vitreous of patients with proliferative diabetic retinopathy compared with nondiabetic control patients.…”
Section: Introductionmentioning
confidence: 99%
“…Yilmaz and coworkers [26] reported a fivefold elevation of NO in the vitreous of patients with proliferative diabetic retinopathy compared with nondiabetic control patients. Given that NO levels are increased in diabetic retinopathy [23][24][25][26], coupled with our findings that NO can upregulate system x c -transporter in RPE cells [4], we asked whether this transporter is present in ganglion cells and if so, whether it is upregulated by NO in these cells.…”
Section: Introductionmentioning
confidence: 99%